Infective endocarditis in the East coast of peninsular Malaysia: a two year retrospective survey from Kuantan - Rathor, Mohammad Yousuf; How, Soon Hin; Abdul Rani, Mohd Fauzi; Shah, Asadullah (National Databases of Indian Medical Journals, 2006)
Infective endocarditis (IE) remains a life threatening infection that is virtually always fatal if untreated. Despite advances in early diagnosis and treatment, several studies have reported an increase in the incidence of IE with notable changes in the nature of underlying cardiac disease. Degenerative, prosthetic, iatrogenic valvular disease and IE among intravenous drug users (IVDU) are now reported more frequently than rheumatic heart disease. The objective of this study was to determine the frequency of IE, its predisposing factors, microbiological status, and outcome at a state hospital in eastern Malaysia. Sixty seven inpatients diagnosed as IE or suspected IE from June 2000 till July 2002 were identified from hospital records out of which 45 cases that fulfilled the Duke criteria for diagnosis were included in the present study. The patients’ predisposing factors, clinical findings, complications, results of investigations and data on clinical outcome were extracted. There were 44 male and 1 female cases with a mean age of 31.9 years, of which 86.7% were IVDUs. Fifteen of our patients were HIV positive, all of whom were IVDU. There was no statistically .significant difference in bacteriology and echocardiography findings among HIV-positive and HIV-negative patients. Among IVDU, Staphylococcus aureus was the most common organism (61.5%) followed by streptococci (17.9%). Among non-IVDU, streptococci were isolated in 66.6 % cases, and Staphylococcus aureus in 1 case (16.6%). All cases were treated medically and median follow up was 6 months. A successful outcome was seen in 91% of patients. Conclusion: Intravenous drug use is the commonest predisposing factor for IE among our patients.